Peasantry and neoextractivism in São Paulo: dynamics and conflicts of the sugar-energy industry in the region of Ribeirão Preto - Corrêa, Victor Marchesin; Carvalho, Joelson Gonçalves de (Universidade Federal de São Carlos, 2024)
Esta pesquisa investigou a dinâmica produtiva do agronegócio canavieiro e seus efeitos na reprodução social de grupos camponeses na Região Administrativa de Ribeirão Preto, interior do estado de São Paulo, importante território hegemonizado pela cana-de-açúcar e palco de diversos conflitos agrários do estado. Para tanto, foram realizadas entrevistas semiestruturadas com agentes representativos para o tema em questão, além de visitas de campo e análise de dados secundários. A partir de um paradigma histórico-dialético, o objetivo deste artigo é demonstrar que, na região em questão, se localiza uma intensiva e predatória atividade neoextrativista protagonizada pelo setor sucroenergético que, em sua lógica de produção, desorganiza e dificulta a produção e reprodução social camponesa. As conclusões indicam que, ainda que fora de zonas de fronteira, há severos impactos sobre grupos camponeses locais, resultando em despossessões, concentração fundiária e conflitos de diversas ordens.

This research has investigated the productive dynamics of the sugarcane agribusiness and its effects on the social reproduction of peasant groups in the administrative region of Ribeirão Preto, in the interior of São Paulo, an important territory hegemonized by sugarcane, which has been the stage of several agrarian conflicts in the state. To pursue this, semi-structured interviews were conducted with representative agents for the topic at hand, as well as field visits and analysis of secondary data. Using a historical-dialectical paradigm, the aim of this article is to demonstrate that in the region in question, an intensive, predatory neoextractivist activity is located, led by the sugarcane sector which, in its production logic, disrupts and hinders peasant production and social reproduction. The conclusions indicate that, even outside frontier zones, there have been severe impacts on local peasant groups, resulting in dispossession, land concentration, and conflicts of various kinds
Keywords: Agribusiness; Sugarcane sector; Socio-environmental impacts; Agrarian issues; Rural settlements; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA RURAL